Design, Development, and Evaluation of a Laboratory-Scale Phytoremediation System Using Eichhornia Crassipes for the Treatment of Chromium-Contaminated Waters - Carreño Sayago, Uriel Fernando; Granada Torres, Carlos Arturo (TECCIENCIA, 2017)
Tanneries have become a serious environmental problem due to the lack of cheap water treatment options in the sector. A viable alternative is to implement the macrophyte aquatic plant (Eichhornia crassipes), which has an extensive presence in bodies of water in Cundinamarca, Colombia. The plant has a high invasive capacity, growing uncontrollably in wetlands, lakes, etc. It has the capacity to accumulate and transform organic matter and, especially, to accumulate metals heavy in its morphology. For this study we designed and built a biological (phytoremediation) treatment system for the removal and uptake of chromium in tannery wastewater in the San Benito sector of southern Bogotá. Eichhornia crassipes was the agent of retention of these pollutant compounds, and we concluded that the use of this plant is an economical and technologically feasible solution for the tannery industry.